Impact of Motivation on Employee Job Satisfaction: With Special Reference to Health Workers during the COVID-19 Pandemic - AROOSIYA, Mrs. MACF.; ITHREES, Mr. A.G. IMAM MOHAMED; FARWIS, M. (The journal of contemporary issues in business and government, 2021)
The objectives of this study were to identify the level of the motivation and job satisfaction of health workers in Sri Lanka, to study the relationship between motivation and job satisfaction, to study the relationship between motivation and dimensions of job satisfaction, to study the relationship between dimensions of motivation and job satisfaction and to explain the ways of improving motivation factors to increase the job satisfaction. To analyze this condition, three hypotheses were formulated. The study was conducted by using a random sample of 100 numbers of Doctors, Nursing Officers and Midwives live in Nintavur. The type of investigation was correlational and it was cross-sectional on time horizon. Doctors, Nursing Officers, and Midwives who live in Nintavur served as respondents for this study. Measures of the study were of good quality after assuring reliability and validity. Data were collected from 100 respondents which were 100% response rate. To test the hypotheses that were concerned with the relationship between the perceived degree of Motivation and perceived degree of Job satisfaction, the Pearson Product Movement Correlation technique was applied. The results of the study showed a significant and positive relationship (r =.807, p=.000) between the perceived degree of Motivation and perceived degree of Job satisfaction.